Changing the Victorian Subject - Tonkin, Maggie; Treagus, Mandy; Seys, Madeleine; Crozier-De Rosa, Sharon (University of Adelaide Press, 2014)
The essays in this collection examine how both colonial and British authors engage with Victorian subjects and subjectivities in their work. Some essays explore the emergence of a key trope within colonial texts: the negotiation of Victorian and settler-subject positions. Others argue for new readings of key metropolitan texts and their repositioning within literary history. These essays work to recognise the plurality of the rubric of the 'Victorian' and to expand how the category of Victorian studies can be understood.